Program Respon untuk Meminimalisir Kekerasan (Seksual) Pada Lokasi Pengungsian Merapi Di Kabupaten Sleman - Sinuraya, Suci Iriani (Prodi Ilmu Pemerintahan, Universitas AMIKOM Yogyakarta, 2023)
This research aims to study Sleman Regency Gender’s Response Program best practice on how they can decrease the (sexual) violence risk to the vulnerable group in the disaster camps. The policy started by involving the Office of Women's Empowerment and Child Protection (DP3AP2KB) into the Disaster Command System Management led by Regional Agency for Disaster Management (BPBD) Sleman under the law: Keputusan Bupati Sleman Nomor 17 tahun 2020 tentang Renkontijensi Bencana Gunung Api Merapi. This research uses qualitative descriptive with case study method refer to Sleman practices. Data collecting from literature studies, observation and indepth interview to informans related. The efforts taken by Sleman Regency, succeed in reducing complains and eliminate bad news about (sexual) violence to the vulnerable in disaster camps. Best practice from Sleman regency hopefully can be an inspiration for a conceptual framework for another region in decreasing vulnerable threat and risk for all disaster kind.